The effectiveness of the four-step jigsaw and jigsaw learning model in improving students' argumentation skills about salt hydrolysis concept - Windy Kartika; Asrial Asrial; Muhammad Haris Effendi-Hasibuan (Jurnal Pendidikan Kimia (JPKim), 2021)
One of the learning models that can train students in developing argumentation skills is the jigsaw learning and its modified forms. This study aimed to see the effectiveness of the four-step jigsaw learning and the Jigsaw learning in improving students' argumentation skills about the concept of salt hydrolysis. This study was conducted with 2 classes of 11 grade students of SMAN 7 Kerinci Jambi. Some 53 students in total were purposively recruited and participated in this experiment. Concurrent embedded mixed method with two-group pretest-posttest control group design was used in this study. The results of independent t-test showed that 4SJ was more effective than the Jigsaw class (t= 2.668; p-value = 0.01 < 0.05). It was supported by the n-Gain of 4SJ which was 0.71 and the n-Gain of jigsaw was 0.67. Two factors that influenced the differences in students' argumentation skills were observed; these included the difference in learning duration and the intensiveness in conducting the argumentation debate. Keywords: argumentation ability, four-step jigsaw, jigsaw, salt hydrolysis